Dampak Bencana Alam Terhadap Perekonomian Masyarakat di Kabupaten Tanah Datar - Decky Dwi Utomo; Fitri Yul Dewi Marta (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2022)
Natural disasters have many negative impacts including infrastructure damage, disease outbreaks, social and economic problems. This research is motivated by the vulnerability of the community's economic condition to disasters in the Tanah Datar area. This study aims to examine the economic vulnerability of the community through modeling to analyze the level of community vulnerability by analyzing the study data on the disaster in the Tanah Datar Regency. This study uses a qualitative descriptive-an approach. Based on the results of this study, there are various potential disasters in Tanah Datar Regency. Potential disasters are based on disaster events that have occurred and the possibility of other disaster events, disasters can also slow down the pace of the economy, especially for victims, even though they are temporary, especially those whose impacts reach trillions of rupiah, for example, money used for development is used to help disaster victims who have lost property so that both the regional and central governments must spend large enough State or Local Budget (APBN/APBD) funds to compensate for the loss.